Hypophysitis following Treatment with Ustekinumab: Radiological and Pathological Findings - Ramos-Leví, Ana M.; Gargallo, Manuel; Serrano-Somavilla, Ana; Sampedro-Núñez, Miguel A.; Fraga, Javier; Marazuela, Monica (Frontiers in Endocrinology, 2018)
Context Ustekinumab is a human IgG1 monoclonal antibody that targets interleukin (IL)-12 and IL-23, which may be useful in the treatment of autoimmune conditions such as psoriasis, psoriatic arthritis and Crohn’s disease. Hypophysitis is an immune-derived inflammatory condition of the pituitary gland that may lead to pituitary dysfunction. With the increasing use of immunotherapy, it is possible that this and other new immune-related adverse events (IRAEs) arise, although the mechanisms involved are still incompletely defined. Case description A 35-year-old male, with a previous history of severe plaque-psoriasis who had started treatment with ustekinumab four months before, complained of progressive and persistent headache. Brain magnetic resonance imaging (MRI) was unremarkable. One year later, a new MRI was performed due to headache persistence, which revealed a homogenous and diffuse pituitary enlargement, with supra-sellar extension and optic quiasm involvement, blurring of the pituitary stalk, absence of clear differentiation between the anterior and posterior lobes, and no signs of hemorrhage or adenomas. Endocrine evaluation was consistent with panhypopituitarism. Work-up of infiltrative and infectious diseases was negative. Follow-up MRI revealed an increase in the pituitary enlargement and transsphenoidal surgery was performed. Pathological findings revealed an intense fibrosis and a chronic inflammatory infiltrate, but no evidence of adenoma, granuloma or acid fast bacilli. Immuno-histochemical staining showed a combined T-cell (CD3+, CD4+) and B-cell (CD19+, CD20+) phenotype. Conclusion We suggest a novel IRAE of ustekinumab, with full radiological and immuno-pathological iconography, which may be mediated by the complex interaction between different immunological processes.